Correction of a designed building's heat balance according to its real heat consumption - Čiuprinskas, Kęstutis; Martinaitis, Vytautas (Journal of Civil Engineering and Management, 2003)
One of the most important issues in the implementation of energy saving measures is a proper evaluation of possible energy savings. If energy savings are overestimated in an energy audit (EA), a situation may occur where after the renovation, the implemented energy saving measures is not paid back or their pay back time is longer than expected before the funds (mostly loaned) were invested. To avoid such a situation, the procedure of a building's energy audit should involve the correction of calculated heat balance according to its real heat consumption, recalculated to the nonnative conditions. In manipulating different building parameters of not exact meanings, it is necessary to attain that the building's heat demand before renovation (theoretically calculated by the same methodology and parameters as demand after renovation) would be as close as possible to the actual heat consumption, recalculated under normative conditions. Only after such a fitting of the actual and theoretical heat demands (decomposition of building heat balance and correction of its components) is it possible to have a reasonable assessment of the feasible heat savings, after the implementation of heat saving measures. The aim of this work is to disclose some peculiarities of building heat balance that is used for energy audit calculations of existing buildings, to offer a calculation methodology evaluating these peculiarities, to show evidently the importance of the investigated problem.First Published Online: 26 Jul 2012